Hubungan Riwayat ASI Eksklusif dengan Kejadian Stunting pada Anak Balita di Puskesmas Purwantoro I. - Viviandita, Jesian; Kisnawaty, Sudrajah Warajati; Widiyaningsih, Endang Nur; Rakhma, Luluk Ria (Media Gizi Ilmiah Indonesia, 2023)
Stunting is a malnutrition for a long time. Malnutrition will cause growth retardation disorders. The percentage of stunting under five nutritional status in Indonesia in 2021 is 24.4%. The factors that cause stunting is infants not getting exclusive breastfeeding. The aim of the study to determine the relationship between history of exclusive breastfeeding on the incidence of stunting in toddlers aged 24-59 months in the working area of Purwantoro I Health Center, Wonogiri Regency. This type of research is Cross Sectional. The sample for this study was toddlers aged 24-59 months who had met the inclusion criteria. The research subjects were 59 people spread across the work area of the Purwantoro I Health Center. The sampling technique was proportional cluster random sampling. History of exclusive breastfeeding was obtained from secondary data from the Purwantoro I Health Center. Data on stunting events were measured based on the nutritional status of children under five obtained from measurements using a microtoise. The data obtained were tested using the Chi Square test. History of toddlers receiving exclusive breastfeeding (0-6 months) was 67.8% and children who did not receive exclusive breastfeeding (0-6 months) were 32.2%. The relationship between history of exclusive breastfeeding and stunting in infants aged 24-59 months was p=0.005. There is a relationship between history of exclusive breastfeeding on the incidence of stunting in toddlers aged 24-59 months in the working area of Purwantoro I Health Center